Cellulose nanocrystals supported-PolyHIPE foams for low-temperature latent heat storage applications - Mert, Hatice Hande; Mere, Hatice Hande; Mert, Emine Hilal; Ocak, Hale; Mert, Mehmet Selcuk (WILEY, 2022)
Paraffin-based shape-stabilized composite phase change materials (PCM) containing surface modified cellulose nanocrystals (CNCs) for thermal energy storage applications were prepared. In this respect, a three-step experimental procedure consisting nanoparticle modification, macroporous foam synthesis, and composite PCM preparation was implemented. While CNCs were modified via freeze-templating, high internal phase emulsion (HIPE) templating was used for the synthesis of polymeric foams - known as polyHIPEs. Meanwhile a simple method was applied to impregnate n-hexadecane (HD), which is a paraffin-based PCM within the polyHIPE foam matrix. It was demonstrated that surface modified CNCs can be efficiently used to prepare polyHIPE foams with improved properties. It was also shown that the impregnation of HD into the -polyHIPE foam matrix supported by CTAB-CNCs can be achieved with an incorporation rate of up to 55.7%. Moreover, the phase transition temperature and thermal energy storage capacity of the obtained composite PCM was determined as 22.7 degrees C and 117 J/g, respectively.
Keywords: cellulose nanocrystals; n-hexadecane; phase change material; polyHIPE; thermal energy storage; PHASE-CHANGE MATERIALS; Polymer Science